Individual participant data meta-analyses should not ignore clustering - Abo-Zaid, Ghada; Guo, Boliang; Deeks, Jonathan J.; Debray, Thomas P.A.; Steyerberg, Ewout W.; Moons, Karel G.M.; Riley, Richard David (Elsevier, 2013)
Objectives